1996
DOI: 10.1097/00005373-199604000-00015
|View full text |Cite
|
Sign up to set email alerts
|

1,000 Consecutive Ultrasounds for Blunt Abdominal Trauma

Abstract: Diagnostic peritoneal lavage (DPL) and computed tomography (CT) are the primary diagnostic modalities used in the evaluation of patients with suspected blunt abdominal trauma (BAT). DPL is fast and accurate but is associated with complications. CT is also accurate, yet requires stability and transportability of the patients. Ultrasound (US) has been suggested as an aid in evaluating BAT. We evaluated US in the initial assessment of BAT in 1000 patients. Patients were eligible for the study if they met specifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
92
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(100 citation statements)
references
References 19 publications
4
92
0
4
Order By: Relevance
“…In blunt trauma studies investigating FAST scanning, outcomes have demonstrated an average specificity of 90 -99% and sensitivity of 86 -99%. [4][5][6][7][8] Sensitivity in this study was therefore comparable. In accordance with previous evidence, our study also demonstrated excellent specificity of FAST (100%) regardless of mechanism of injury.…”
Section: Discussionsupporting
confidence: 55%
“…In blunt trauma studies investigating FAST scanning, outcomes have demonstrated an average specificity of 90 -99% and sensitivity of 86 -99%. [4][5][6][7][8] Sensitivity in this study was therefore comparable. In accordance with previous evidence, our study also demonstrated excellent specificity of FAST (100%) regardless of mechanism of injury.…”
Section: Discussionsupporting
confidence: 55%
“…[8][9][10] Beyond the ED, ultrasonography for trauma assessment has been adopted by military personnel for field use 22 and as a screening test in mass-casualty situations. 23,24 Although bedside ultrasonography has become a modality taught in both adult surgical and emergency medicine residency programs, 15,16 this has not translated into the pediatric training environment.…”
Section: Discussionmentioning
confidence: 99%
“…EDUS has been shown to be useful in adults as a screening modality for suspected IAI, [8][9][10] with a recent randomized controlled trial showing a 64% reduction in time to operative care compared to CT alone. 11 The applicability of EDUS in children is less well established.…”
mentioning
confidence: 99%
“…In 3 studies, as a decision making tool for the need for laparotomy in hypotensive patients (BP <90 systolic ), FAST had a sensitivity of 100%, specificity of 96% and a negative predictive value of 100% (Wherret et al, Rozycki et al, McKenny et al) In the detection of free intra-abdominal fluid when compared to a reference standard such as DPL/CT or laparotomy, FAST had a sensitivity of 75%, a specificity of 98% and a negative predictive value of 98%(18 studies, 6324 patients, 1992 to 2000) [9][10][11]. The minimum amount of fluid that can be detected is 70 -250mls depending on the study [12].…”
Section: Pregnant Womenmentioning
confidence: 99%